Organization Of Innovative Activities Through Distance Education - Saidova Mohinur Jonpolatovna (Zien Journals, 2023)
This article describes the content of using the design process and the use of integrated cognitive methods to achieve an effective result in training the future elementary school teacher in practical activities through distance education.
Keywords: Distance education; elementary school; future elementary school teacher; design